PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI MODERASI (STUDI KASUS PADA PERUSAHAAN FARMASI DI INDONESIA) - Pebisitona Mesajaya Purba (Program Studi Ilmu Ekonomi, 2023)
Abstract The purpose of this study was to determine the effect of profitability and company size on firm value and to determine the effect of company size in moderating the relationship between profitability and firm value in pharmaceutical companies from 2018 to 2021. This study used multiple linear regression analysis using a 3-model approach. The sample used in this study was 40 data, which were selected using purposive sampling method. The results showed that profitability as measured by net profit margin has a positive and significant effect on firm value. Company size as assessed by total assets has a positive and significant effect on firm value. Firm size is able to strengthen the relationship between profitability and firm value.